An alternative to derive ionospheric and tropospheric SSR corrections for PPP-RTK using adaptive constraints - de Oliveira, Paulo Sergio (2023)
PPP-RTK (Precise Point Positioning–Real Time Kinematic) is a positioning method by GNSS (Global Navigation Satellite Systems), based on the SSR (State Space Representation) concept. One challenge for the fast convergence of PPP-RTK solutions in real-time applications is the mitigation of atmospheric effects (troposphere and ionosphere). Thus, using atmospheric models, PPP solutions can achieve accurate positions and shortened initialisation time. Such performance depends on the topology of permanent station networks and atmospheric conditions. The main objective of this contribution is to study the PPP-RTK and the optimised infrastructure in terms of costs and benefits to realise the method using atmospheric corrections.